2023
DOI: 10.1186/s12889-023-15195-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors combine in a complex manner in assessment for macrosomia

Abstract: Background Macrosomia is a serious public health concern. This study aimed to examine the combined effects of various risk factors on macrosomia. Methods The China Labor and Delivery Survey was a multicenter cross-sectional study that included 96 hospitals. Logistic regression analysis was performed to examine the combined effects of the risk factors for macrosomia. The population attributable risk percentage (PAR%) was calculated for the risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Maternal age over 35 years old is also considered a risk factor for macrosomia 8 . Furthermore, pre‐pregnancy overweight, and obesity contribute to the occurrence of macrosomia 9 . Macrosomia babies are significantly more susceptible to brachial plexus injuries during delivery, with a 20‐fold higher risk compared to babies with normal birth weights 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal age over 35 years old is also considered a risk factor for macrosomia 8 . Furthermore, pre‐pregnancy overweight, and obesity contribute to the occurrence of macrosomia 9 . Macrosomia babies are significantly more susceptible to brachial plexus injuries during delivery, with a 20‐fold higher risk compared to babies with normal birth weights 10 .…”
Section: Discussionmentioning
confidence: 99%
“… 8 Furthermore, pre‐pregnancy overweight, and obesity contribute to the occurrence of macrosomia. 9 Macrosomia babies are significantly more susceptible to brachial plexus injuries during delivery, with a 20‐fold higher risk compared to babies with normal birth weights. 10 A significant concern in preventing brachial plexus palsy is the evident link between this condition and macrosomia in diabetic mothers.…”
Section: Discussionmentioning
confidence: 99%
“…This allows for earlier and more targeted interventions, potentially preventing the onset of obesity rather than merely attempting to reverse it [28,30,[43][44][45]. Furthermore, predictive analytics can help monitor the effectiveness of prescribed interventions in real-time, allowing for adjustments that improve outcomes [25,39,46,47]. Moreover, as obesity continues to be a…”
Section: Discussionmentioning
confidence: 99%
“…Obesity, characterized by excessive fat accumulation, poses serious health risks and challenges, but ML offers innovative solutions for both its understanding and management [32,52]. By integrating ML into obesity research, scientists and healthcare providers can analyse large, diverse data sets to identify patterns and predictors of obesity that are not immediately apparent through conventional statistical methods [40,46]. One of the primary applications of ML in the context of obesity is in the development of predictive models [5,13].…”
Section: Discussionmentioning
confidence: 99%
“…5 Macrosomic babies delivered vaginally were found to be more likely to predispose to adverse-feto-maternal complications like perineal tear, post-partum haemorrhage, anal sphincter injury, need for blood transfusion, asphyxia neonatorum, obstructed labour, birth trauma neonatal hypoglycemia and NICU admission. 6,7 Thus Nguyen et al suggested the need to curate the mode of delivery and consider elective caesarean delivery when foetal macrosomia is known or suspected. 10 While caesarean section reduces the incidence of some of the above mentioned complications associated with vaginal birth in cases of foetal macrosomia, the risks are eliminated entirely.…”
Section: Introductionmentioning
confidence: 99%